Implementación de un sistema de control y monitoreo para la radiación ultravioleta en la universidad técnica de Cotopaxi en el periodo marzo 2019 – agosto 2019. - Cañizares Guerrero, Bryan Patricio (2019)
In order to technology could be immersed in programming and controlling, this technological proposal wants to implement a system to monitor the ultraviolet radiation at Technical University of Cotopaxi (UTC) through exposing data in real time reflected in a web page, a mobile application and a numeric screen to reference the solar radiation levels, following the recommendations of the World Health Organization (WHO). Additionally, this system will also have a database that can be used through a web page or directly from the removable memory, which will periodically record the measurements made every half hour, the system will have two solar panels and a bank of two batteries connected in series to the corresponding power supply of its elements. By an arduino mega 2560 and arduino one microprocessors, the system will process the meteorological data such as radiation, temperature and humidity emitted by its sensors. The data will additionally be stored in a physical memory where all the measurements made could be stored to be used when necessary; this device will be linked through an internet network which will permit a constant updating of the web page and of the mobile application. This device will be located in a strategic place, where the influx of people is the largest, so that anyone who visits this location can know the level of radiation that he is exposed and, likewise, link this level with the measures of protection that should be taken, according to each case; in this way, this project aims to raise people awareness about health care, and provide the electrical engineering career laboratory with a record of historical data on the behavior of UV radiation, and in this way, it will be possible to do evaluation practices of the estimated power in the designing of photovoltaic systems or any other use to the extracted real data.